PENGARUH RASIO KEUANGAN DALAM MEMPREDIKSI KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Anggun Putri Romadhina; Eka Kusuma Dewi (LPPM Universitas Putera Batam, 2023)
This study aims to obtain empirical evidence regarding the effect of liquidity ratios, leverage, activity, profitability and sales stability on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. There were 50 companies that were indicated to be experiencing financial distress so that they were delisted from the Indonesia Stock Exchange during 2017-2021, one of the reasons being that they had been declared bankrupt/bankrupt and the opportunity to live was disrupted. This is a threat that can be experienced by all companies regardless of the type or size of the company and can occur at any time. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) which issued financial reports during 2017-2021. . The samples obtained based on the purposive sampling method amounted to 50 sample data of observational data. The data analysis technique in this study is multiple linear regression. The results of this study indicate that the liquidity ratio, leverage ratio, profitability and sales growth have a significant effect on financial distress. Meanwhile, the activity ratio has no significant effect on financial distress.